FEEDER WIRA WIRI SUROBOYO SEBAGAI SALAH SATU UPAYA MEWUJUDKAN SURABAYA SMART CITY - Sari, Ika Novita (Tata Kota dan Daerah, 2023)
The number of residents and vehicles in Surabaya continues to increase every year, resulting in overcrowding and accidents. For this reason, the Surabaya city government launched Wira Wiri Suroboyo to reduce traffic jams. The purpose of this writing is to find out the implementation of aspects of the smart cityconcept through smart mobility and sustainable transportation on the Wira Wiri Suroboyo feeder . The method in this research is qualitative with a descriptive approach. The method used in analyzing is literature study with secondary data collection techniques originating from news, collections of books or previous research journals related to the issues discussed. The results of the study show that the implementation of aspects of the smart cityconcept through smart mobility indicators in Wira Wira Suroboyo still needs to be further developed. Based on economic indicators, Wira Wiri Suroboyo is capable of becoming sustainable transportation, while in terms of social and environmental aspects it still needs further development so that it can become friendly transportation for persons with disabilities and is able to reduce traffic jams and density in Surabaya.